The Impact of the Method Extraction and Different Carrot Variety on the Carotenoid Profile, Total Phenolic Content and Antioxidant Properties of Juices - Purkiewicz, Aleksandra (Plants (Basel), 2020)
The study assesses the antioxidant activity (AA), carotenoid profile and total phenolic content (TPC) of carrot juices obtained from three different varieties (black, orange and yellow) and prepared using high- (HSJ) and low-speed juicer (LSJ). The AA assessment was carried out using four assays (DPPH, ABTS, PCL ACW and PCL ACL). The content of carotenoids was conducted by high performance liquid chromatography equipped with a diode array detector (HPLC-DAD) method, while the total phenolic content by the spectrophotometric method. It was shown that orange carrot juices contain more carotenoids than yellow and black carrot juices, approximately ten and three times more, respectively. The total carotenoid content in orange carrot juice made by the HSJ was higher (by over 11%) compared to juice prepared by the LSJ. The highest total phenolic content was noticed in black carrot juices, while the lowest in orange carrot juices. In black carrot juices, a higher range of TPC was found in juices made by HSJ, while in the case of the orange and yellow carrots, the highest content of TPC was detected in juices prepared by the LSJ. AA of the juices was highly dependent on the carrot variety, juice extraction method. The most assays confirmed the highest AA values in black carrot juices. Furthermore, it was shown that the HSJ method is more preferred to obtain orange and yellow carrot juices with higher antioxidant properties, while the LSJ method is more suitable for black carrot juice extraction.